Is Simvastatin Associated with Oral Lichenoid Drug Reaction? - Thongprasom, Kobkan (Journal of Dentistry Indonesia, 2018)
Currently, various drugs have been found to induce many oral lesions. Some medications used to treat systemic diseases can affect the oral mucosa and induce lesions known as oral lichenoid drug reaction (OLDR). The diagnosis is made when the oral lesion errupted after the patient took a specific medication. However, diagnosis is challenging when a patient takes multiple medications and the onset of the eruption is unclear. OLDRs commonly cause severe pain in the oral cavity and affect the quality of life. Statins are widely used by patients with cardiovascular disease (CVD) to lower blood cholesterol levels, decreasing the risk of heart attack or stroke. This review will focus the side effects of a hypolipidemic drug group (statins) in the oral cavity. From previous experience, simvastatin may be related to severe oral ulcerations, dysplasia, and carcinoma in situ in the oral mucosa. Moreover, simvastatin combined with amlodipine can induce more severe oral lesions that are very difficult to treat. Therefore, the beneficial effect of these drugs and their side effects should be considered carefully, because simvastatin significantly affects oral and general health.